Keadilan Restoratif dan Kepastian Hukum dalam Syarat Penghentian Penuntutan: Telaah Yuridis Peraturan Kejaksaan Nomor 15 Tahun 2020 - Ismail Uno; Lion Hidjun; Siti Rahmawaty Igirisa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2026)
This study aims to analyze the legal requirements for the termination of prosecution based on restorative justice as stipulated in Article 5 of the Regulation of the Attorney General of the Republic of Indonesia Number 15 of 2020 and to examine its juridical implications for legal certainty within the Indonesian criminal justice system. This research employs a normative juridical method using both a statutory approach and a conceptual approach, supported by primary, secondary, and tertiary legal materials. The collected legal materials were analyzed qualitatively using a descriptive-analytical method focusing on the legal norms governing the termination of prosecution based on restorative justice. The findings indicate that Article 5 establishes both objective and subjective legal requirements that serve as normative limitations on the exercise of prosecutorial authority to terminate prosecutions under the restorative justice mechanism. Nevertheless, several provisions are formulated as open-textured legal norms without clear operational parameters, thereby failing to satisfy the principle of legal certainty fully. This condition gives rise to juridical implications, including the expansion of prosecutorial discretion and the potential for inconsistent interpretation in determining whether the legal requirements for the termination of prosecution have been fulfilled. Therefore, it is necessary to strengthen the formulation of these legal norms by establishing clearer, more measurable parameters and harmonizing the regulation with the national criminal procedural law framework to ensure greater legal certainty in the implementation of restorative justice-based termination of prosecution.